(untitled) (Contemporary Journal of Social Science Review, 2026)
The expansion of digital communication has changed the ways second language learners engage with English. Among these developments, microblogging platforms such as Twitter/X and Threads provide spaces for written interaction and language use beyond the classroom. This study examines the impact of microblogging platforms on ESL learners’ writing fluency and vocabulary acquisition. The study is informed by Lev Vygotsky’s Sociocultural Theory, with particular attention to the concepts of social interaction and the Zone of Proximal Development (ZPD). A quantitative research design was used, with data collected from university-level ESL learners through structured close-ended questions and one open-ended question. Participants had experience using microblogging platforms ranging from six months to two years. The data were analyzed to explore the relationship between microblogging use and language learning outcomes. The findings show that learners who regularly use microblogging platforms demonstrate improvement in writing fluency and vocabulary acquisition. These learners report greater ease in expressing ideas in written English and a broader use of vocabulary. Frequent users also indicate lower levels of writing anxiety compared to less active users. In addition, microblogging platforms appear to support motivation for writing, with learners engaging in more frequent written communication than in traditional classroom settings. The study suggests that microblogging platforms can be used as supportive tools in ESL learning environments to promote writing practice and vocabulary development through social interaction.